MODERATION VILLAGE: THE IMPLEMENTATION OF RELIGIOUS MODERATION PORTRAIT AT INTERFAITH FAMILY - Noor Fatikah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This research is aimed to analyze the implementation of religious moderation in a family and its role to shape young generation moderate behavior. The case study was conducted on a family in Ngoro (Moderation Village) Jombang, whose members come from different religious backgrounds. A qualitative approach was used with data collection techniques through in-depth interviews and observation. The research results showed that that families have succeeded to implement the religious values ?? moderation through respecting differences of beliefs, increasing interfaith understanding, managing emotions wisely, opening constructive dialogue and avoiding religious coercion. This implementation has brought many positive benefits such as preventing conflict, building harmony and improving the quality of family life. Besides, the family played a very important role in shaping the younger generation moderate character through providing role models, values ??education, and cultivating a harmonious family environment even though they come from different religious backgrounds